Bone-forming peptide-2 derived from BMP-7 enhances osteoblast differentiation from multipotent bone marrow stromal cells and bone formation - Kim, Hyung Keun (Exp Mol Med, 2017)
Strategies for efficient osteogenic differentiation and bone formation from stem cells would have clinical applications in treating nonunion fracture healing. Many researchers have attempted to develop adjuvants as specific stimulators of bone formation for therapeutic use in patients with bone resorption. Therefore, development of specific stimulators of bone formation has therapeutic significance in the treatment of osteoporosis. To date, investigations of the mature forms of bone morphogenetic proteins (BMPs) have focused on regulation of bone generation. However, we previously identified new peptides from the immature precursor of BMP, and further analysis of these proteins should be performed. In this study, we identified a new peptide called bone-forming peptide-2 (BFP-2), which has stronger osteogenic differentiation-promoting activity than BMP-7. BFP-2 treatment of multipotent bone marrow stromal cells (BMSCs) induced expression of active alkaline phosphatase. In addition, BFP-2 enhanced CD44 and CD51 expression levels and increased Ca(2+) content in BMSCs. Moreover, radiography at 8 weeks revealed that animals that had received transplants of BFP-2-treated BMSCs showed substantially increased bone formation compared with animals that had received BMSCs treated with BMP-7. Our findings indicate that BFP-2 may be useful in the development of adjuvant therapies for bone-related diseases.